MULTILEVEL MODELING FOR ANALYZING EDUCATION SYSTEM IN YTU - Noyan, Fatma; Yildiz, Dogan (YILDIZ TECHNICAL UNIV, 2006)
Multilevel modeling which is often used in social sciences for analyzing data has a hierarchical or clustered structure, for instance in educational research where pupils nested within schools. A crucial problem in the statistical analysis of hierarchically structured data is the dependence of the observations at the lower levels. Multilevel models account for this dependence and in recent years these models have been widely accepted. We apply the multilevel analysis approach to the YTU 2002-2003 educational data and the aim is to 'investigate the academicians' performance in Yildiz Technical University. These data with a two level structure consist of students nested within different departments. The objective of this analysis is to assess if there is a significant difference in mean academicians effectiveness across departments.
Keywords: Multilevel modeling; hieararchical linear models; random coefficient models; Engineering